A Two-Stage Continuous Fermentation System for Conversion of Syngas into Ethanol - Hanno Richter; Michael E. Martin; Largus T. Angenent (Energies, 2013)
We have established a two-stage continuous fermentation process for production of ethanol from synthesis gas (syngas) with Clostridium ljungdahlii. The system consists of a 1-L continuously stirred tank reactor as a growth stage and a 4-L bubble column equipped with a cell recycle module as an ethanol production stage. Operating conditions in both stages were optimized for the respective purpose (growth in stage one and alcohol formation in stage two). The system was fed with an artificial syngas mixture, mimicking the composition of syngas derived from lignocellulosic biomass (60% CO, 35% H2, and 5% CO2). Gas recycling was used to increase the contact area and retention time of gas in the liquid phase, improving mass transfer and metabolic rates. In stage two, the biocatalyst was maintained at high cell densities of up to 10 g DW/L. Ethanol was continuously produced at concentrations of up to 450 mM (2.1%) and ethanol production rates of up to 0.37 g/(L·h). Foam control was essential to maintain reactor stability. A stoichiometric evaluation of the optimized process revealed that the recovery of carbon and hydrogen from the provided carbon monoxide and hydrogen in the produced ethanol was 28% and 74%, respectively.